Cohort mortality study of workers at seven beryllium processing plants: update and associations with cumulative and maximum exposure. Issue 5 (15th October 2010) - Schubauer-Berigan, Mary K; Couch, James R; Petersen, Martin R; Carreón, Tania; Jin, Yan; Deddens, James A
Abstract : Objectives: To extend follow-up of cause-specific mortality in workers at seven beryllium processing plants and to estimate associations between mortality risk and beryllium exposure. Methods: 9199 workers were followed for mortality from 1940 through 2005. Standardised mortality ratios (SMRs) were estimated based on US population comparisons for lung, nervous system and urinary tract cancers, chronic obstructive pulmonary disease (COPD), chronic kidney disease, and categories containing chronic beryllium disease (CBD) and cor pulmonale. Associations with maximum and cumulative exposure were calculated for a subset of the workers. Results: Overall mortality in the cohort compared with the US population was elevated for lung cancer (SMR 1.17; 95% CI 1.08 to 1.28), COPD (SMR 1.23; 95% CI 1.13 to 1.32), and the categories containing CBD (SMR 7.80; 95% CI 6.26 to 9.60) and cor pulmonale (SMR 1.17; 95% CI 1.08 to 1.26). Mortality rates for most diseases of interest increased with time-since-hire. For the category including CBD, rates were substantially elevated compared to the US population across all exposure groups. Workers whose maximum beryllium exposure was ≥10 μg/m 3 had higher rates of lung cancer, urinary tract cancer, COPD and the category containing cor pulmonale than workers with lower exposure. Significant positive trends with cumulative exposure were observed for nervous system cancers (p=0.0006) and, when short-term workers were excluded, lung cancer (p=0.01), urinary tract cancer (p=0.003) and COPD (p<0.0001). Conclusion: These findings reaffirm that lung cancer and CBD, and suggest that COPD and nervous system and urinary tract cancers, are related to beryllium exposure. Cigarette smoking and exposure to other lung carcinogens are unlikely to explain these elevations.